2018
DOI: 10.1021/acs.jafc.8b01621
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Relationship between Intestinal Colostrum or Milk, and Serum Metabolites in Neonatal Calves by Metabolomics Analysis

Abstract: In contrast to colostral immunoglobulins, changes in metabolite composition of ingested colostrum in the gut have received little attention. Here, we characterized the metabolite profiles of colostrum and milk, ingested colostrum and milk, and serum of neonatal calves by liquid chromatography tandem-mass spectrometry and gas chromatography-mass spectrometry metabolomics approaches. Colostrum and milk underwent similar changes in metabolite profiles in the gut after being ingested. These changes were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Other studies have demonstrated that serum concentrations of glycine, histidine, lysine, and serine were associated with diverging RFI of different broiler chicken lines which may be attributed to their contributions to protein biosynthesis and ammonia recycling [52,53]. Additionally, certain organic acids, such as 4-aminobutyric acid, 3phenylpropanoic acid, and phenylacetic acid are involved in many biological processes: modulating glucose and lipid metabolism, regulating energy homeostasis, and exerting antioxidant, anti-inflammatory, and neuroprotective actions [54][55][56]. Thus, such breed-associated metabolites, which may be correlated with the health status and production traits of meat rabbits, could be considered as candidate biomarkers for breed improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that serum concentrations of glycine, histidine, lysine, and serine were associated with diverging RFI of different broiler chicken lines which may be attributed to their contributions to protein biosynthesis and ammonia recycling [52,53]. Additionally, certain organic acids, such as 4-aminobutyric acid, 3phenylpropanoic acid, and phenylacetic acid are involved in many biological processes: modulating glucose and lipid metabolism, regulating energy homeostasis, and exerting antioxidant, anti-inflammatory, and neuroprotective actions [54][55][56]. Thus, such breed-associated metabolites, which may be correlated with the health status and production traits of meat rabbits, could be considered as candidate biomarkers for breed improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Animal care and use procedures were approved by the Animal Care Advisory Committee of the Anhui Academy of Agricultural Sciences. Male calves from multiparous Holstein cows at Chuzhou dairy farm (Chuzhou, China) were selected for this study, and the detailed experimental procedures were characterized in our previous study (Qi et al, 2018;Zhao et al, 2018). In brief, the animals were divided into 3 groups: the control group (CT) comprising 3 calves that were not fed colostrum or milk, the colostrum group (CO) comprising 3 calves that received 2 colostrum meals at 1 to 2 h and 10 to 12 h after birth, and the milk group (MK) comprising 3 calves that received 2 milk meals at 1 to 2 h and 10 to 12 h after birth.…”
Section: Animals and Sample Collectionmentioning
confidence: 99%
“…Glucose supply is clearly improved in colostrum-fed calves compared with calves fed a formula with the same lactose content as colostrum but much lower amounts of biologically active factors (Steinhoff-Wagner et al, 2011;Gruse et al, 2015). Colostrum intake affects the neonatal metabolome, indicating large systemic effects on neonatal metabolism after first colostrum intake (Hammon et al, 2012;Qi et al, 2018;Zhao et al, 2018). Furthermore, thermoregulatory mechanisms, including the metabolism of brown adipose tissue, shivering, and physical activity, are important for adaptation to new environmental conditions after birth, and colostrum intake stimulates heat production in neonatal calves (Vermorel et al, 1983).…”
Section: Introductionmentioning
confidence: 99%